The prospect of synthesis of PES/PEG blend membranes using blend NMP/DMF for CO2/N2 separation - Fadel Abdul Hadi Juber (14151300) (2022)
Carbon dioxide (CO2) emissions have been the root cause for anthropogenic climate change. Decarbonisation strategies, particularly carbon capture and storage (CCS) are crucial for mitigating the risk of global warming. Among all current CO2 separation technologies, membrane separation has the biggest potential for CCS as it is inexpensive, highly efficient, and simple to operate. Polymeric membranes are the preferred choice for the gas separation industry due to simpler methods of fabrication and lower costs compared to inorganic or mixed matrix membranes (MMMs). However, plasticisation and upper-bound trade-off between selectivity and permeability has limited the gas separation performance of polymeric membranes. Recently, researchers have found that the blending of glassy and rubbery polymers can effectively minimise trade-off between selectivity and permeability. Glassy poly(ethersulfone) (PES) and rubbery poly(ethylene) glycol (PEG) are polymers that are known to have a high affinity towards CO2. In this paper, PEG and PES are reviewed as potential polymer blend that can yield a final membrane with high CO2 permeance and CO2/nitrogen (N2) selectivity. Gas separation properties can be enhanced by using different solvents in the phase-inversion process. N-Methyl-2-Pyrrolidone (NMP) and Dimethylformamide (DMF) are common industrial solvents used for membrane fabrication. Both NMP and DMF are reviewed as prospective solvent blend that can improve the morphology and separation properties of PES/PEG blend membranes due to their effects on the membrane structure which increases permeation as well as selectivity. Thus, a PES/PEG blend polymeric membrane fabricated using NMP and DMF solvents is believed to be a major prospect for CO2/N2 gas separation. Other Information Published in: Journal of Polymer Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10965-021-02500-6